2018
DOI: 10.1186/s12870-018-1335-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitro sucrose on quality components of tea plants (Camellia sinensis) based on transcriptomic and metabolic analysis

Abstract: BackgroundTea plants [Camellia sinensis (L.) O. Kuntze] can produce one of the three most widely popular non-alcoholic beverages throughout the world. Polyphenols and volatiles are the main functional ingredients determining tea’s quality and flavor; however, the biotic or abiotic factors affecting tea polyphenol biosynthesis are unclear. This paper focuses on the molecular mechanisms of sucrose on polyphenol biosynthesis and volatile composition variation in tea plants.ResultsMetabolic analysis showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 105 publications
2
23
0
Order By: Relevance
“…Phenolic synthesis requires carbohydrates, which explains the sharp increase in phenolic concentration in the presence of high sucrose observed in this experiment. A similar effect was also observed in Camellia sinensis plants in vitro (Qian et al 2018). Therefore, sucrose might play a role in birch in vitro shoot recalcitrance and lowered sucrose concentration might be beneficial during rejuvenation.…”
Section: Discussionsupporting
confidence: 70%
“…Phenolic synthesis requires carbohydrates, which explains the sharp increase in phenolic concentration in the presence of high sucrose observed in this experiment. A similar effect was also observed in Camellia sinensis plants in vitro (Qian et al 2018). Therefore, sucrose might play a role in birch in vitro shoot recalcitrance and lowered sucrose concentration might be beneficial during rejuvenation.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, the transcript levels of the CsWD40 gene were significantly upregulated under sucrose and ABA stresses, but no response was found to mannitol, NaCl, and SA (Salicylicacid) stresses under different temperatures. Our previous study showed that under ABA and sucrose stresses the most flavonoid was accumulated and the related gene expression increased [ 43 ]. This result suggests CsWD40 promotes the accumulation of products of the flavonoid biosynthetic pathway, which led to stress tolerance in tea plants.…”
Section: Discussionmentioning
confidence: 99%
“…The primers used are listed in Table S1 . The vectors were constructed and the genetic transformation of tobacco was performed according to the method of Li et al [ 43 ]. The phenotypes of transgenic plants growing in the controlled environment chamber were recorded to characterize the effect of transgene overexpression on growth.…”
Section: Methodsmentioning
confidence: 99%
“…Using gene ontology (GO) analysis, the DEPs were classified into three categories: cellular components (CC), molecular function (MF) and biological processes (BP) [19]. During the early phase of cold stress in both cultivars, the most highly represented categories were 'cell', 'cell part', 'intracellular', 'intracellular part' and 'cytoplasm' in CC (Fig.…”
Section: Primary Functional Classification Of Depsmentioning
confidence: 99%